Window Dressing in Stoneybatter: Net Curtains, Parlour Rooms and Changing Demographics in an Urban Village - Orla Fitzpatrick (Review of Irish Studies in Europe, 2019)
This paper will examine patterns and trends in domestic window dressing in the Stoneybatter area of Dublin with particular reference to the terraced houses built by the Dublin Artisan’s Dwelling Company (D.A.D.C.) between 1890 and 1900. The tradition of adorning and embellishing the windows of these small homes reveals much about notions of respectability, taste and class in this changing and increasingly gentrified community. Traditionally ornaments, souvenirs, plants and miscellaneous bric-a-brac were placed in front windows, positioned in such a way to face the passer-by, and these were generally framed by patterned net curtains. Gentrification and shifting demographic patterns mean that the generations of skilled artisans and those employed by large local institutions (the Guinness Brewery, military and medical institutions) have been replaced by a diverse range of people whose tastes and treatment of their homes differs to their predecessors. This window-dressing, whilst not a uniquely Irish or Dublin phenomenon, is a type of self-expression and creativity which has received little attention within the Irish context and especially within the urban setting. A review of the historiography of Dublin reveals that until recent years there was a focus upon the extremes of poverty and wealth, and that design history has not sufficiently addressed the tastes of stable, working communities such as those resident in the Stoneybatter area.